Methods for measurement-based COTS assessments and selection - Cechich, Alejandra (2002)
During recent years, new software engineering paradigms like component-based software engineering and COTS-based development have emerged. Both paradigms are concerned with reuse and customisation of existing components. The use of COTS software has become more and more important in state-of-the-art and state-of-the-practice software and system development. Using COTS software promises faster time-to-market, which can yield substantial advantages over competitors with regards to earlier placement of a new product on a market. At the same time, COTS software introduces risks such as unknown quality properties of the COTS software in use that can inject harmful side effects into the final product. In this paper, we present a brief comparison of well-known COTS evaluation methods. Our work is focused on identifying the main goals and features of the methods in order to extend their uses on evaluating COTS products as well as COTS development processes.